South Africa: A comparative analysis of the economic status of Muslim and Non-Muslim Indians in the Durban Municipal Area - Padayachee, M. (Journal / Institute of Muslim Minority Affairs, King Abdulazis University, 1984)
The purpose of this paper is to present the results of the 'Income and Employment Survey of Indians in Municipal Durban' (1980). It includes data on dwellings, ownership of dwellings, household monthly income, occupation, dependency, and education